The Incidence of Contrast-Induced Nephropathy Following Computed Tomography and Associated Risk Factors - Reza Mosaddegh; Fatemeh Mohammadi; Aydin Mohammad Valipour; Seyed Mohammad Hosseini; Mobin Naghshbandi; Mobina Yarahmadi; Nazanin Alaei Faradonbeh (Radiology Research and Practice)
Conclusion: 8.8% of patients developed CIN following contrast administration. Among risk factors, the only effectual risk factor was the initial serum creatinine level.